2019
DOI: 10.1021/acsanm.9b00089
|View full text |Cite
|
Sign up to set email alerts
|

Spiral Graphene Nanoribbons with Azulene Defects as Potential Nonlinear Optical Materials

Abstract: Inducing new nonlinear optical (NLO) properties while keeping the thermal stability of carbon-based nanomaterials paves a new path for the application of carbon nanomaterials in optoelectronics. In the present work, azulene units are introduced to spiral carbon nanoribbons to enhance the polarity of the charge distribution in spiral carbon nanoribbons, significantly enhancing the first hyperpolarizabilities of those nanoribbons and making the nanoribbons potential nonlinear optical materials. For example, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…Here the large 6-311+G(d) Pople split-valence basis set is used combined with the CAM-B3LYP. In favor of usingthe PCM model, recent theoretical studies of NLO properties of molecules immersed in solvent media have shown a good agreement with the experimental data for the Hyper-Rayleigh Scattering first hyperpolarizability [5,13,21,25].…”
Section: Solvent Mediamentioning
confidence: 71%
“…Here the large 6-311+G(d) Pople split-valence basis set is used combined with the CAM-B3LYP. In favor of usingthe PCM model, recent theoretical studies of NLO properties of molecules immersed in solvent media have shown a good agreement with the experimental data for the Hyper-Rayleigh Scattering first hyperpolarizability [5,13,21,25].…”
Section: Solvent Mediamentioning
confidence: 71%
“…, azulene-embedded nanographene 26,27 and azulene-defected GNRs. 21,28 In this work, the designed X-type molecules are polyacene based molecules with azulenes at four end-corners (Fig. 1) and similar systems have been successfully synthesized.…”
Section: Models and Computational Detailsmentioning
confidence: 99%
“…Accordingly, considerable efforts have been devoted toward synthesizing and predicting carbon based molecules fused with azulenes in various patterns, e.g., azulene-embedded nanographene 26,27 and azulene-defected GNRs. 21,28 In this work, the designed X-type molecules are polyacene based molecules with azulenes at four end-corners (Fig. 1) and similar systems have been successfully synthesized.…”
Section: Models and Computational Detailsmentioning
confidence: 99%
“…The sum-over-state (SOS) approach will be used to calculate the second hyperpolarizability. The SOS approach has been widely used to calculate the second molecular hyperpolarizability in organic compounds [49][50][51][52][53][54][55][56][57][58][59]. The benefit of the SOS approach is that it truncates the sum of states, as the significant contribution occurs in only a few excited states.…”
Section: Nonlinear Optical Propertiesmentioning
confidence: 99%